Burden of asthma with elevated blood eosinophil levels. Issue 1 (December 2016) - Casciano, Julian; Krishnan, Jerry; Small, Mary; Buck, Philip; Gopalan, Gokul; Li, Chenghui; Kemp, Robert; Dotiwala, Zenobia
Abstract Background Asthma is a common chronic condition with an economic burden of almost $56 billion annually in the US. Biologic markers like blood eosinophils, that help predict the risk of exacerbation could help guide more optimal treatment plans and reduce cost. The purpose of this study was to determine whether healthcare resource use and expenditures vary by eosinophil level among patients with asthma. Methods Patients with a diagnosis of asthma defined by ICD-9-CM code 493.xx between January 2004 and July 2011 were extracted from EMRClaims + database (eMAX Health, White Plains NY). Patients were classified as mild, moderate, or severe by medication use following diagnosis, based on recommendations of National Institutes of Health Expert Panel Report 3. Patients were classified as those with elevated eosinophils (≥400 cells/μL) and normal eosinophil level (<400 cells/μL). Patients were followed for resource use, defined as hospitalizations, ER visits and outpatient visit and associated costs were calculated to assess whether an economic difference exists between eosinophil groups. Non-parametric tests were used to compare resource use and associated cost between elevated and normal eosinophil groups. Multivariate modeling was performed to assess the contribution of eosinophil level on the likelihood of study outcomes among patients with severe asthma. Results Among the 2, 164 patients meeting eligibility criteria, 1, 144 had severity designations. Of these, 179(16 %) of patients had severe asthma of which 20 % (n  = 35) had elevated eosinophils. Seventeen percent of patients with elevated eosinophils were admitted to the hospital during the follow-up period, significantly greater than patients with normal eosinophil levels (12 %;p  = 0.011). Overall, compared to patients with normal eosinophil levels (n  = 1734), patients with elevated eosinophil levels (n  = 430) had significantly greater mean annual hospital admissions (0.51 vs. 0.21/year, p  = 0.006) and hospital costs (2, 536 vs. $1, 091, p  = 0.011). Logistic regressions showed that elevated eosinophil level was associated with 5.14 times increased odds of all cause admissions (95 % CI:1.76–14.99, p  = 0.003) and 4.07 times increased odds of asthma related admissions (95 % CI: 1.26–13.12, p  = 0.019). Conclusion Eosinophil elevation was associated with greater healthcare resource use in patients with asthma.